Biceps tendon rupture diagnosed by physical examination and ultrasonography in the emergency department - Tiryaki Baştuğ, Betül; Subaşı, Berkay; Gök, Pakize Gözde; Parpucu, Kübra; Genç, Eşref (The European Research Journal, 2018)
A biceps brachii rupture can occur at either superior or inferior end but most commonly involves the long head at its proximal attachment to superior glenoid labrum. We report a 48-year-old male with a proximal long-head biceps rupture because of trauma diagnosed by ultrasonography and physical examination in the emergency department. On physical examination, there was a severe pain over the anterior aspect of the shoulder, proximal part of the biceps muscle, and distally located biceps muscle mass. In ultrasonographic study, there were no tendon fibers in the right shoulder bicipital groove. The evaluation of both the physical examination and sonographic findings revealed a proximal long-head biceps rupture.